Dedifferentiated Fat (DFAT) cells: A cell source for oral and maxillofacial tissue engineering. (24th April 2018) - Kishimoto, N; Honda, Y; Momota, Y; Tran, SD
Abstract : Tissue engineering is a promising method for the regeneration of oral and maxillofacial tissues. Proper selection of a cell source is important for the desired application. This review describes the discovery and usefulness of dedifferentiated fat (DFAT) cells as a cell source for tissue engineering. Dedifferentiated Fat cells are a highly homogeneous cell population (high purity), highly proliferative, and possess a multilineage potential for differentiation into various cell types under proper in vitro inducing conditions and in vivo. Moreover, DFAT cells have a higher differentiation capability of becoming osteoblasts, chondrocytes, and adipocytes than do bone marrow‐derived mesenchymal stem cells and/or adipose tissue‐derived stem cells. The usefulness of DFAT cells in vivo for periodontal tissue, bone, peripheral nerve, muscle, cartilage, and fat tissue regeneration was reported. Dedifferentiated Fat cells obtained from the human buccal fat pad (BFP) are a minimally invasive procedure with limited esthetic complications for patients. The BFP is a convenient and accessible anatomical site to harvest DFAT cells for dentists and oral surgeons, and thus is a promising cell source for oral and maxillofacial tissue engineering.